Corallopyronin A Specifically Targets and Depletes Essential Obligate Wolbachia Endobacteria From Filarial Nematodes In Vivo - Schiefer, Andrea (Oxford University Press, 2012)
Doxycycline and rifampicin deplete essential Wolbachia from filarial nematodes that cause lymphatic filariasis or onchocerciasis, resulting in blocked worm development and death. However, doxycycline is contraindicated for children and pregnant/breastfeeding women, as is rifampicin in the latter group with the additional specter of possible resistance development in Mycobacterium spp. Novel antibiotics with a narrower spectrum would aid in eliminating filarial diseases. Corallococcus coralloides synthesizes corallopyronin A, a noncompetitive inhibitor of RNA polymerase ineffective against Mycobacterium spp. Corallopyronin A depleted Wolbachia from infected insect cells (1.89 Thus the antibiotic is effective against intracellular bacteria despite the many intervening surfaces (blood vessels, pleura, worm cuticle) and membranes (worm cell, vesicle, Wolbachia inner and outer membranes). Corallopyronin A is an antibiotic to develop further for filariasis elimination without concern for cross-resistance development in tuberculosis.